2017
DOI: 10.1177/0956797617705386
|View full text |Cite
|
Sign up to set email alerts
|

Resisting Temptation: Tracking How Self-Control Conflicts Are Successfully Resolved in Real Time

Abstract: Across four studies, we used mouse tracking to identify the dynamic, on-line cognitive processes that underlie successful self-control decisions. First, we showed that individuals display real-time conflict when choosing options consistent with their long-term goal over short-term temptations. Second, we found that individuals who are more successful at self-control-whether measured or manipulated-show significantly less real-time conflict in only self-control-relevant choices. Third, we demonstrated that succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 38 publications
2
80
0
Order By: Relevance
“…This is especially relevant to self‐regulation research, as such goal‐related decisions often occur automatically (i.e., in a few hundred milliseconds) and sometimes even unconsciously (see Lopez, Stillman, Heatherton, & Freeman, for a more detailed review). For example, research using mouse tracking to assess self‐control conflict found that people generally experience conflict when choosing between goal‐congruent (e.g., healthy food) and more tempting (e.g., unhealthy food) options (relative to a comparison group; e.g., food vs. non‐food item); however, those with higher levels of trait self‐control experienced less conflict (Stillman, Medvedev, & Ferguson, ). One limitation to this paradigm, however, is that mouse‐tracking has so far been restricted to making dichotomous decisions on a screen, which limits external validity (e.g., asking participants to indicate which food they prefer while displaying a picture of unhealthy food in one corner of the screen and a picture of healthy food in the other; Sullivan, Hutcherson, Harris, & Rangel, ).…”
Section: Finding the Middle Groundmentioning
confidence: 99%
“…This is especially relevant to self‐regulation research, as such goal‐related decisions often occur automatically (i.e., in a few hundred milliseconds) and sometimes even unconsciously (see Lopez, Stillman, Heatherton, & Freeman, for a more detailed review). For example, research using mouse tracking to assess self‐control conflict found that people generally experience conflict when choosing between goal‐congruent (e.g., healthy food) and more tempting (e.g., unhealthy food) options (relative to a comparison group; e.g., food vs. non‐food item); however, those with higher levels of trait self‐control experienced less conflict (Stillman, Medvedev, & Ferguson, ). One limitation to this paradigm, however, is that mouse‐tracking has so far been restricted to making dichotomous decisions on a screen, which limits external validity (e.g., asking participants to indicate which food they prefer while displaying a picture of unhealthy food in one corner of the screen and a picture of healthy food in the other; Sullivan, Hutcherson, Harris, & Rangel, ).…”
Section: Finding the Middle Groundmentioning
confidence: 99%
“…As suggested by previous research (Freeman et al, 2011;Stillman et al, 2017), the trajectory of the mouse is influenced by the ongoing decisional process, and metrics derived from it can capture conflict based on underlying selfcontrol processes. One conflict metric is the area under the curve (AUC) which reflects the degree of deviation from an ideal trajectory (equivalent to a straight line) to the selected option.…”
Section: Analysis Of Mouse Trajectoriesmentioning
confidence: 99%
“…Additionally, with modeling, Price, Higgs, Maw and Lee (2016) found that intertemporal choice could be well explained by a two-parameter model that depicted the dual-process theory. Moreover, recent studies with mouse-tracking demonstrated that the trajectories were less direct when making less impulsive intertemporal choices, and concluded that participants had to inhibit the temptation of choosing the sooner smaller rewards in order to maximize their benefit in the long run (Cheng & González-Vallejo, 2017;Dshemuchadse, Scherbaum, & Goschke, 2013;Stillman, Medvedev, & Ferguson, 2017).…”
Section: Exploring a Second Version Of Crt: Crt-2mentioning
confidence: 99%